SIGLEC15 amplifies immunosuppressive properties of tumor-associated macrophages in pancreatic cancer - Li, Tian-Jiao; Jin, Kai-Zhou; Li, Hao; Ye, Long-Yun; Li, Peng-Cheng; Jiang, Bruce; Lin, Xuan; Liao, Zhen-Yu; Zhang, Hui-Ru; Shi, Sai-Meng; Lin, Meng-Xiong; Fei, Qing-Lin; et al. (Cancer letters, 2022)
Pancreatic ductal adenocarcinoma (PDAC) usually presents infrequent infiltration of T lymphocytes. The known immune-checkpoint inhibitors to date focus on activating T cells and manifest limited effectiveness in PDAC. SIGLEC15 was identified as a novel tumor-associated macrophage (TAM)-related immune-checkpoint in other cancer types, while its immunosuppressive role and clinical significance remained unclear in PDAC. In our study, SIGLEC15 presented immunosuppressive relevance in PDAC via bioinformatic analysis and expressed on TAM and PDAC cells. SIGLEC15+ TAM, rather than SIGLEC15+ PDAC cells or SIGLEC15- TAM, correlated with poor prognosis and immunosuppressive microenvironment in the PDAC microarray cohort. Compared with SIGLEC15- TAM, SIGLEC15+ TAM presented an M2-like phenotype that could be modulated by SIGLEC15 in a tumor cell-dependent manner. In mechanism, SIGLEC15 interacted with PDAC-expressed sialic acid, preferentially α-2, 3 sialic acids, to stimulate SYK phosphorylation in TAM, which further promoted its immunoregulatory cytokines and chemokines production. In vivo, SIGLEC15+ TAM also presented an M2-like phenotype, accelerated tumor growth, and facilitated immunosuppressive microenvironment, which was greatly abolished by SYK inhibitor. Our study highlighted a novel M2-promoting function of SIGLEC15 and strongly suggested SIGLEC15 as a potential immunotherapeutic target for PDAC. •SIGLEC15 was abundant in PDAC and preferentially expressed on TAM and PDAC cells.•SIGLEC15+ TAM predicted poor prognosis and presented immunosuppressive relevance.•SIGLEC15 supported M2-like TAM in a PDAC cell-dependent manner.•SIGLEC15 interacted with PDAC-expressed sialic acid to stimulate SYK phosphorylation.•SIGLEC15 served as an attractive immunotherapeutic target in PDAC.